The burden, support and needs of primary family caregivers of people experiencing schizophrenia in Beijing communities: a qualitative study - Chen, Lifen; Zhao, Yali; Tang, Juan; Jin, Guanghui; Liu, Yanli; Zhao, Xuexue; Chen, Chao; Lu, Xiaoqin (BMC psychiatry, 2019)
Family caregivers play crucial roles in taking care of people experiencing schizophrenia in the community. The burdens on and needs of caregivers of these patients should be emphasized. This study aimed to explore the perspective of family caregivers of people experiencing schizophrenia in the communities of Beijing in terms of the burdens of care and the acquisition and further need for support in order to provide guidance to health care providers regarding how to target therapeutic interventions for families of individuals experiencing schizophrenia and to provide recommendations for policy makers to tailor countermeasures and services. A total of 20 family caregivers of schizophrenia patients were enrolled in our study. A face-to-face and semi-structured in-depth qualitative interview study was conducted to explore the caregivers' perspective on the burden on caregivers, support and further needs. This study was conducted in the community health service centres where the family caregivers regularly visit. The study was carried out according to good ethical practices, data analysis and reporting guidelines. Most participants reported that they were suffering from heavy life burdens and had negative experiences with respect to obtaining social support, and they emphasized that they would require more support. Economic and daily housework burdens, limited social communication, and psychological stresses were the principal burdens. Support including financial, medical and information and educational support did not satisfy the needs of the caregivers and their patients. More financial support, respect, and rehabilitation institutions were reported to be needs of the caregivers. Family caregivers of people experiencing schizophrenia suffer from heavy physical and psychological burdens; however, the current support provided is insufficient. More services and better public attitudes should be considered for people experiencing schizophrenia and their caregivers.